Table S3, Mass-to-charge ratios (m/z) of precursors and product ions as well as collision energies (CE) of diagnostic transitions during multiple reaction monitoring of heterocyst glycolipids at Quadrupole 1 (Q1) and 3 (Q3) - Felix J Elling; Jordon D Hemingway; Jenan Kharbush; Kevin W Becker; Catherine Ann Polik; Ann Pearson (PANGAEA, 2021)
Heterocyst glycolipids (HGs) were analyzed using an Agilent 1290 ultra high-performance liquid chromatograph coupled to an Agilent 6410 triple quadrupole mass spectrometer equipped with an electrospray ionization interface operated in positive mode, following Wörmer et al. (2012). This work was supported by the Gordon and Betty Moore Foundation.
In: Elling, FJ et al. (2021): Mediterranean sapropel bulk organic matter and biomarker concentrations and carbon isotope compositions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937082